Children and Institutions: US Censuses, Race, Class, and Gender in Puerto Rico’s Institutions for Minors, 1910–1940. - Del Moral, Solsiree; Shin, Enoch (Latin American Research Review, 2026)
The authors examine the 1910, 1920, 1930, and 1940 US censuses to identify demographic characteristics of children who resided in public and private institutions for minors, with special attention to patterns of racial segregation and exclusion. The article focuses on public and private institutions founded exclusively to serve children and youth and also on correctional institutions for children and adults. The authors found racial segregation in private institutions, underrepresentation of children of color in both private and public institutions, and overrepresentation of boys of color in correctional institutions for minors and adults. They also identified a historical pattern, with few exceptions, of excluding girls of color from all types of public and private institutions.